Du concept à la mise en œuvre du développement durable : théorie et pratique autour de guide SD 21000 - Christian Brodhag; Natacha Gondran; Karen Delchet (VertigO)
Corporate social responsibility concept develops within an international institutional framework where public regulations are verging voluntary approaches. The article treats theoretical bases of the voluntary approaches, differences between RSE and sustainable development and the drifts to which a cosmetic approach of sustainable development leads. In conclusion the article shows how SD 21000 guidelines, developed by AFNOR, make it possible to reach beyond the identified limits.